DEVELOPMENT OF LIFE SKILLS OF PEOPLE WITH SPECIAL NEEDS AS A DIRECTION OF SOCIAL ADAPTATION - Калиниченко, Елена (Pedagogy and Psychology, 2021)
The article considers the development of life skills in people with special needs as a direction of social adaptation. According to studies and clinical case reports, a relatively stable picture of problems in social adaptation in children, adolescents and adults with special educational needs is shown. Moreover, there are some indications that subsequent socialization disorders may be associated with inadequately formed life skills. Some of these include inadequate behavioral assessment and a lack of controlled research. It is concluded that future research may focus on: 1) expanding the range of social skills targeted at current programs, 2) preventing social dysfunction in adulthood by increasing the use of life skills, and 3) further research is needed on the role of life skills in the socialization of individuals with special needs.